High-strength wear-resistant aluminum alloy material and preparation process thereof
By adding metal chromium powder, titanium powder and alumina to the aluminum alloy material, and using modified chitosan microspheres and silicone modified polyurethane resin prepolymers, the problem of insufficient strength and wear resistance in high load and harsh environments is solved, and higher strength and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202510052935.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-08
AI Technical Summary
Existing aluminum alloy materials cannot meet higher strength requirements in high-load mechanical operations, harsh climatic conditions or long-term outdoor use scenarios, affecting the stability and safety of the structure, and perform poorly in the face of challenges such as wear and erosion.
The metal permeability diffuser is prepared by adding metal chromium powder, titanium powder and alumina, and thermal permeability treatment is carried out to improve the strength and wear resistance of aluminum alloy sheets. High-performance coatings are prepared to improve corrosion resistance using materials such as modified chitosan microspheres and silicone modified polyurethane resin prepolymers.
It significantly improves the strength, wear resistance and corrosion resistance of aluminum alloy materials, can better adapt to complex usage conditions, and enhances the stability and safety of the structure.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum alloys, in particular to a high-strength wear-resistant aluminum alloy material and a preparation process thereof. Background Art
[0002] Aluminum alloy materials play an increasingly important role in modern industry and life. Their unique physical and chemical properties make them the preferred materials for a variety of applications. From architectural decoration to aerospace, from transportation to electronic equipment, the application of aluminum alloy sheets is ubiquitous, showing their wide value. First of all, aluminum alloy materials have excellent lightweight properties. The density of aluminum alloy is about 2.7g / cm³, which is only one-third of that of steel. This allows the structure using aluminum alloy sheets to significantly reduce its own weight and increase the load capacity of transportation vehicles or the range of aircraft. For example, in the aviation industry, aluminum alloy materials are widely used in aircraft fuselages, wings and other parts to reduce the total weight of the aircraft, improve fuel efficiency and reduce operating costs. In the automotive manufacturing industry, the use of aluminum alloy materials can effectively reduce the weight of the vehicle body, improve fuel economy, and reduce emissions, which is in line with the current development trend of energy conservation and environmental protection. In addition, aluminum alloy materials also have excellent processing properties. Whether it is cold processing or hot processing, products of various shapes can be manufactured according to actual needs through stamping, extrusion, casting and other processes. This not only provides designers with great creative freedom, but also greatly improves production efficiency, reduces production costs, and promotes the rapid development of related industries. For example, in the field of packaging materials, aluminum alloy materials can be easily processed into packaging containers of various shapes and sizes, such as cans, which not only ensures the product's protective function but also meets the aesthetic requirements. In addition, aluminum alloy materials are easy to recycle and reuse, and have a high resource recycling rate. According to statistics, the recycling rate of aluminum alloys can reach more than 95%, and the recycling process has low energy consumption, low emissions, and is environmentally friendly. This is in line with the concept of sustainable development advocated by the current society and helps to build a resource-saving and environmentally friendly society.
[0003] However, for certain specific application environments, such as high-load mechanical operations, harsh climatic conditions, or long-term outdoor use, ordinary aluminum alloy materials may not be able to meet higher strength requirements, and the strength of the material is directly related to the stability and safety of the structure. For example, in the aerospace field, key components such as the wings and fuselage of the aircraft need to withstand huge stress, so the material is required to have extremely high strength to ensure flight safety. Similarly, in the automotive manufacturing industry, the strength of the body structure directly affects the safety performance and collision performance of the vehicle. By strengthening the strength of aluminum alloy materials, these structural parts can provide sufficient support and protection while ensuring lightweight, thereby improving the overall safety standards. Therefore, it is crucial to improve the strength of aluminum alloy sheets. In addition, in many industrial environments, equipment and components will face challenges such as wear and erosion, especially those applications in harsh conditions such as moisture, salt spray, and chemical corrosion. For example, aluminum alloy sheets used in shipbuilding need to be able to resist corrosion from seawater to extend the service life of the hull; while parts in engineering machinery need to have good wear resistance to cope with high-intensity operating environments. By improving the surface treatment technology of aluminum alloy plates, such as anodizing, spraying special coatings and other methods, its wear resistance and corrosion resistance can be significantly improved, so that it can adapt to more complex usage conditions.
[0004] In order to overcome the defects of the prior art, the present invention provides a high-strength wear-resistant aluminum alloy material and a preparation process thereof. Summary of the invention
[0005] The purpose of the present invention is to provide a high-strength wear-resistant aluminum alloy material and a preparation process thereof, so as to solve the problems in the prior art.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: A preparation process of a high-strength wear-resistant aluminum alloy material comprises the following steps: Step 1: Melting and casting the aluminum alloy raw material to obtain an ingot; then subjecting the ingot to high-temperature insulation, extrusion molding, and stretching molding in sequence to obtain an aluminum alloy plate; embedding the aluminum alloy plate in a metal diffusion agent, and after sealing, heating it to 130-150°C for 5-10 minutes, and then heating it to 550-600°C for 3-5 hours, and then cooling it with the furnace to obtain a high-strength aluminum alloy plate; Step 2: Add modified chitosan and acetic acid solution to deionized water, stir well to obtain an aqueous phase; add 3-4% volume of emulsifier Span-80 to paraffin, stir well to obtain an oil phase; mix the aqueous phase and the oil phase, adjust the pH to 8.5-9.5, and then drop vanillin solution to fully cross-link for 6-8 hours. After the reaction is completed, wash and dry to obtain modified chitosan microspheres; add the modified chitosan microspheres to 15-18% sodium tartrate solution, stir well, and then adsorb at low pressure for 6-8 hours. After the adsorption is completed, wash, centrifuge, and vacuum dry to obtain a microcapsule corrosion inhibitor; Step 3: Mix N,N-dimethylformamide, isophorone diisocyanate, hydroxypropyl polydimethylsiloxane, microcapsule corrosion inhibitor and dibutyltin dilaurate, and react at 65-70°C for 4-5 hours to obtain a silicone-modified polyurethane resin prepolymer; mix the silicone-modified polyurethane resin prepolymer, silica filler, dispersant, defoaming agent and leveling agent to obtain a high-performance coating; apply the high-performance coating to the surface of the high-strength aluminum alloy plate, dry at 50-70°C for 2-3 hours, and continue drying at 100-120°C for 2-3 hours to obtain a finished product.
[0007] More optimally, in step one, the contents of the components of the metal diffusion agent are: by mass fraction, 35-40% chromium powder, 20-30% titanium powder, 30-35% aluminum oxide, and the remainder is ammonium chloride.
[0008] More optimally, in step one, the contents of each component of the aluminum alloy raw material are: by mass fraction, 0.8-0.9% magnesium, 1.5-2.0% silicon, 0.1-0.3% iron, 0.2-0.5% zinc, 0.1-0.2% copper, 0.1-0.2% manganese, 0.02-0.03% titanium, 0.02-0.03% chromium, 0.07-0.08% iridium, and the balance is aluminum.
[0009] More optimally, in step one, the high temperature insulation temperature is 450-550°C; the extrusion molding temperature is 500-520°C, and the extrusion speed is 20-30m / min.
[0010] More optimally, in step 2, the preparation process of modified chitosan is as follows: S1: dissolving chitosan in 2.5-3.5% acetic acid solution, dissolving 4-N,N-diethylaminobenzaldehyde in anhydrous ethanol, mixing the two solutions and stirring at 75-80°C for 5-7h, cooling to room temperature after the reaction, adding acetone solution, standing, vacuum drying, and grinding to obtain Schiff alkalized chitosan; S2: Dissolve 1,3-dibromopropane in acetonitrile, dissolve triethylamine in anhydrous ethanol, mix the two solutions and stir at 0-4°C for 2-3h and at 25-30°C for 10-15h. After the reaction, perform rotary evaporation, precipitation, washing and freeze drying to obtain quaternary ammonium bromide; S3: Dissolve the Schiff alkaline chitosan and sodium hydroxide in isopropanol, react at -15~-10℃ for 10-15h, then add quaternary ammonium bromide solution dropwise, react at 25-35℃ for 4-6h, wash and vacuum dry after the reaction to obtain modified chitosan.
[0011] More optimally, when preparing Schiff-base chitosan, the reaction mass ratio of chitosan and 4-N,N-diethylaminobenzaldehyde is 3:(5-6); when preparing quaternary ammonium bromide salt, the reaction molar ratio of 1,3-dibromopropane and triethylamine is 1:(1.0-1.1); when preparing modified chitosan, the reaction mass ratio of Schiff-base chitosan, sodium hydroxide and quaternary ammonium bromide salt is 1:(3.0-3.5).
[0012] More optimally, in step 2, when preparing modified chitosan microspheres, the concentration of the aqueous phase is 3-4wt%, the volume ratio of the aqueous phase to the oil phase is 1:(15-18), and the vanillin solution is 0.003-0.005wt%.
[0013] More optimally, in step three, when preparing the silicone-modified polyurethane resin prepolymer, the reaction mass ratio of isophorone diisocyanate, hydroxypropyl polydimethylsiloxane, microcapsule corrosion inhibitor and dibutyltin dilaurate is 8:80:(15-20):0.1.
[0014] More optimally, in step three, the contents of the components of the high-performance coating are: by mass, 50-60 parts of silicone-modified polyurethane resin prepolymer, 20-30 parts of silica filler, 2-3 parts of dispersant, 2-3 parts of defoamer, and 3-5 parts of leveling agent.
[0015] Beneficial effects of the present invention: The feature of the present invention is that in step one, a metal diffusion agent is prepared by adding metal chromium powder, titanium powder and aluminum oxide; the metal diffusion agent is applied to the surface of the aluminum alloy plate by thermal diffusion to obtain a high-strength aluminum alloy plate. By adding metal chromium powder, on the one hand, the hardness of the aluminum alloy surface can be significantly improved, and its wear resistance and scratch resistance can be enhanced; on the other hand, the diffusion of chromium elements can enhance the lattice structure of the aluminum alloy substrate, thereby improving its tensile strength and yield strength. By adding metal titanium powder, on the one hand, titanium powder can significantly improve the strength and toughness of the aluminum alloy, so that it maintains good mechanical properties under high temperature and high stress environment; on the other hand, titanium powder can form a stable compound with the aluminum alloy substrate, further enhancing its corrosion resistance.
[0016] The present invention is characterized in that, in step 2, by adding chitosan and 4-N,N-diethylaminobenzaldehyde, Schiff-base chitosan is obtained; by adding 1,3-dibromopropane and triethylamine, a nucleophilic substitution reaction occurs to obtain a quaternary ammonium bromide salt; the Schiff-base chitosan and the quaternary ammonium bromide salt are mixed in an alkaline environment, a hydroxyl-halogen substitution reaction occurs, and the quaternary ammonium bromide salt is introduced into the surface of the Schiff-base chitosan to obtain a modified chitosan. Furthermore, by adding the modified chitosan as the aqueous phase and adding paraffin as the oil phase, a modified chitosan microsphere is prepared. The sodium tartrate solution is introduced into the structure of the modified chitosan microsphere by low-pressure adsorption to obtain a microcapsule corrosion inhibitor. Adding the microcapsule corrosion inhibitor to the coating in step three can significantly improve the corrosion resistance of the coating. The reasons are analyzed as follows: on the one hand, the surface of the modified chitosan microsphere structure contains Schiff base structure and quaternary ammonium salt structure, which significantly improves the antibacterial and corrosion resistance of chitosan; on the other hand, sodium tartrate is also a good corrosion inhibitor. When the corrosion on the surface of the aluminum alloy plate invades the interior of the coating and destroys the chitosan microsphere structure, the sodium tartrate corrosion inhibitor will be released to further resist corrosion.
[0017] The present invention is characterized in that in step 3, by adding isophorone diisocyanate, hydroxypropyl polydimethylsiloxane, microcapsule corrosion inhibitor and dibutyltin dilaurate, a silicone-modified polyurethane resin prepolymer is obtained, and then various additives are added to obtain a high-performance coating. The high-performance coating contains a large amount of components such as silicone, polyurethane, and microcapsule corrosion inhibitor, so it has excellent wear resistance and corrosion resistance, so the high-performance coating is applied to the surface of a high-strength aluminum alloy plate to obtain a high-strength wear-resistant finished product. DETAILED DESCRIPTION
[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] Source of raw materials: Chitosan, deacetylation degree 95%, purchased from MacLean reagent; propyl polydimethylsiloxane, JHY-10, purchased from Jiande Polymer New Materials Co., Ltd.; defoamer, brand BYK141, purchased from BYK Chemical Company; leveling agent, brand BYK333, purchased from BYK Chemical Company; dispersant, brand BYK110, purchased from BYK Chemical Company.
[0020] Embodiment 1: Step 1: Melting and casting the aluminum alloy raw material to obtain an ingot; then the ingot is sequentially subjected to high temperature insulation, extrusion molding, and stretching molding to obtain an aluminum alloy plate; the aluminum alloy plate is embedded in a metal diffusion agent, and after sealing, the temperature is first raised to 150°C for insulation for 10 minutes, and then the temperature is raised to 600°C for insulation for 5 hours, and a high-strength aluminum alloy plate is obtained after furnace cooling; the content of each component of the metal diffusion agent is: by mass fraction, 35% chromium powder, 25% titanium powder, 30% alumina, and 10% ammonium chloride; the content of each component of the aluminum alloy raw material is: by mass fraction, 0.9% magnesium, 2.0% silicon, 0.3% iron, 0.5% zinc, 0.2% copper, 0.2% manganese, 0.03% titanium, 0.03% chromium, 0.08% iridium, and 95.76% aluminum; the high temperature insulation temperature is 550°C; the extrusion molding temperature is 520°C, and the extrusion speed is 30m / min; Step 2: S1: dissolve chitosan in 3.5% acetic acid solution, dissolve 4-N,N-diethylaminobenzaldehyde in anhydrous ethanol, mix the two solutions and stir at 80°C for 7h, cool to room temperature after the reaction, add acetone solution, stand, vacuum dry and grind to obtain Schiff alkalized chitosan; the reaction mass ratio of chitosan to 4-N,N-diethylaminobenzaldehyde is 3:5; S2: Dissolve 1,3-dibromopropane in acetonitrile and triethylamine in anhydrous ethanol, mix the two solutions and stir at 4°C for 3h and 30°C for 15h. After the reaction, perform rotary evaporation, precipitation, washing and freeze drying to obtain quaternary ammonium bromide; the reaction molar ratio of 1,3-dibromopropane to triethylamine is 1:1; S3: Dissolve the Schiff alkaline chitosan and sodium hydroxide in isopropanol, react at -10°C for 15h, then dropwise add quaternary ammonium bromide solution, react at 35°C for 6h, wash and vacuum dry after the reaction to obtain modified chitosan; the reaction mass ratio of Schiff alkaline chitosan, sodium hydroxide and quaternary ammonium bromide is 1:3.2; S4: Add modified chitosan and acetic acid solution to deionized water, stir well to obtain water phase; add 4% volume of emulsifier Span-80 to paraffin, stir well to obtain oil phase; mix the water phase and oil phase, adjust pH to 9.5, then drop vanillin solution to fully cross-link for 8 hours, wash and dry after the reaction to obtain modified chitosan microspheres; add modified chitosan microspheres to 18% sodium tartrate solution, stir well, adsorb at low pressure for 8 hours, wash, centrifuge and vacuum dry after adsorption to obtain microcapsule corrosion inhibitor; the concentration of water phase is 3.5wt%, the volume ratio of water phase to oil phase is 1:16, and the vanillin solution is 0.004wt%; Step 3: Mix N,N-dimethylformamide, isophorone diisocyanate, hydroxypropyl polydimethylsiloxane, microcapsule corrosion inhibitor and dibutyltin dilaurate, and react at 70°C for 5 hours to obtain a silicone-modified polyurethane resin prepolymer; mix 60g of silicone-modified polyurethane resin prepolymer, 30g of silica filler, 3g of dispersant, 3g of defoaming agent, and 5g of leveling agent to obtain a high-performance coating; apply the high-performance coating to the surface of the high-strength aluminum alloy plate, dry at 70°C for 3 hours and continue to dry at 120°C for 3 hours to obtain a finished product; the reaction mass ratio of isophorone diisocyanate, hydroxypropyl polydimethylsiloxane, microcapsule corrosion inhibitor and dibutyltin dilaurate is 8:80:16:0.1.
[0021] Embodiment 2: Step 1: Melting and casting the aluminum alloy raw material to obtain an ingot; then the ingot is sequentially subjected to high temperature insulation, extrusion molding, and stretching molding to obtain an aluminum alloy plate; the aluminum alloy plate is embedded in a metal diffusion agent, and after sealing, the temperature is first raised to 140°C for insulation for 8 minutes, and then the temperature is raised to 570°C for insulation for 4 hours, and the high-strength aluminum alloy plate is obtained after furnace cooling; the content of each component of the metal diffusion agent is: by mass fraction, 35% chromium powder, 25% titanium powder, 30% alumina, and 10% ammonium chloride; the content of each component of the aluminum alloy raw material is: by mass fraction, 0.9% magnesium, 2.0% silicon, 0.3% iron, 0.5% zinc, 0.2% copper, 0.2% manganese, 0.03% titanium, 0.03% chromium, 0.08% iridium, and 95.76% aluminum; the high temperature insulation temperature is 500°C; the extrusion molding temperature is 510°C and the extrusion speed is 25m / min; Step 2: S1: dissolve chitosan in 3% acetic acid solution, dissolve 4-N,N-diethylaminobenzaldehyde in anhydrous ethanol, mix the two solutions and stir at 77°C for 6 hours, cool to room temperature after the reaction, add acetone solution, stand, vacuum dry and grind to obtain Schiff alkalized chitosan; the reaction mass ratio of chitosan to 4-N,N-diethylaminobenzaldehyde is 3:5.5; S2: Dissolve 1,3-dibromopropane in acetonitrile and triethylamine in anhydrous ethanol, mix the two solutions and stir at 2°C for 2.5h and 27°C for 13h. After the reaction, perform rotary evaporation, precipitation, washing and freeze drying to obtain quaternary ammonium bromide; the reaction molar ratio of 1,3-dibromopropane to triethylamine is 1:1; S3: Dissolve the Schiff alkaline chitosan and sodium hydroxide in isopropanol, react at -13°C for 12h, then dropwise add quaternary ammonium bromide solution, react at 30°C for 5h, wash and vacuum dry after the reaction to obtain modified chitosan; the reaction mass ratio of Schiff alkaline chitosan, sodium hydroxide and quaternary ammonium bromide is 1:3.2; S4: Add modified chitosan and acetic acid solution to deionized water, stir well to obtain water phase; add 3.5% volume of emulsifier Span-80 to paraffin, stir well to obtain oil phase; mix the water phase and oil phase, adjust pH to 9, then drop vanillin solution to fully cross-link for 7 hours, wash and dry after the reaction to obtain modified chitosan microspheres; add modified chitosan microspheres to 16% sodium tartrate solution, stir well, adsorb at low pressure for 7 hours, wash, centrifuge and vacuum dry after adsorption to obtain microcapsule corrosion inhibitor; the concentration of water phase is 3.5wt%, the volume ratio of water phase to oil phase is 1:17, and the vanillin solution is 0.004wt%; Step 3: Mix N,N-dimethylformamide, isophorone diisocyanate, hydroxypropyl polydimethylsiloxane, microcapsule corrosion inhibitor and dibutyltin dilaurate, and react at 67°C for 4.5 hours to obtain a silicone-modified polyurethane resin prepolymer; mix 60g of silicone-modified polyurethane resin prepolymer, 30g of silica filler, 3g of dispersant, 3g of defoaming agent, and 5g of leveling agent to obtain a high-performance coating; apply the high-performance coating to the surface of the high-strength aluminum alloy plate, dry at 60°C for 2.5 hours and continue to dry at 110°C for 2.5 hours to obtain a finished product; the reaction mass ratio of isophorone diisocyanate, hydroxypropyl polydimethylsiloxane, microcapsule corrosion inhibitor and dibutyltin dilaurate is 8:80:17:0.1.
[0022] Embodiment 3: Step 1: Melting and casting the aluminum alloy raw material to obtain an ingot; then the ingot is sequentially subjected to high temperature insulation, extrusion molding, and stretching molding to obtain an aluminum alloy plate; the aluminum alloy plate is embedded in a metal diffusion agent, and after sealing, the temperature is first raised to 130°C for insulation for 5 minutes, and then the temperature is raised to 550°C for insulation for 3 hours, and a high-strength aluminum alloy plate is obtained after furnace cooling; the content of each component of the metal diffusion agent is: by mass fraction, 35% chromium powder, 25% titanium powder, 30% alumina, and 10% ammonium chloride; the content of each component of the aluminum alloy raw material is: by mass fraction, 0.9% magnesium, 2.0% silicon, 0.3% iron, 0.5% zinc, 0.2% copper, 0.2% manganese, 0.03% titanium, 0.03% chromium, 0.08% iridium, and 95.76% aluminum; the high temperature insulation temperature is 450°C; the extrusion molding temperature is 500°C, and the extrusion speed is 20m / min; Step 2: S1: dissolve chitosan in 3% acetic acid solution, dissolve 4-N,N-diethylaminobenzaldehyde in anhydrous ethanol, mix the two solutions and stir at 75°C for 5h, cool to room temperature after the reaction, add acetone solution, stand, vacuum dry and grind to obtain Schiff alkalized chitosan; the reaction mass ratio of chitosan to 4-N,N-diethylaminobenzaldehyde is 3:5.5; S2: Dissolve 1,3-dibromopropane in acetonitrile and triethylamine in anhydrous ethanol, mix the two solutions and stir at 0°C for 2h and 25°C for 10h. After the reaction, perform rotary evaporation, precipitation, washing and freeze drying to obtain quaternary ammonium bromide; the reaction molar ratio of 1,3-dibromopropane to triethylamine is 1:1; S3: Dissolve the Schiff alkaline chitosan and sodium hydroxide in isopropanol, react at -15°C for 10 hours, then dropwise add quaternary ammonium bromide solution, react at 25°C for 4 hours, wash and vacuum dry after the reaction to obtain modified chitosan; the reaction mass ratio of Schiff alkaline chitosan, sodium hydroxide and quaternary ammonium bromide is 1:3.2; S4: Add modified chitosan and acetic acid solution to deionized water, stir well to obtain water phase; add 3% volume of emulsifier Span-80 to paraffin, stir well to obtain oil phase; mix the water phase and oil phase, adjust pH to 8.5, then drop vanillin solution for full cross-linking reaction for 6 hours, wash and dry after the reaction to obtain modified chitosan microspheres; add modified chitosan microspheres to 15% sodium tartrate solution, stir well, adsorb at low pressure for 6 hours, wash, centrifuge and vacuum dry after adsorption to obtain microcapsule corrosion inhibitor; the concentration of water phase is 3wt%, the volume ratio of water phase to oil phase is 1:16, and the vanillin solution is 0.003wt%; Step 3: Mix N,N-dimethylformamide, isophorone diisocyanate, hydroxypropyl polydimethylsiloxane, microcapsule corrosion inhibitor and dibutyltin dilaurate, and react at 65°C for 4 hours to obtain a silicone-modified polyurethane resin prepolymer; mix 60g of silicone-modified polyurethane resin prepolymer, 30g of silica filler, 3g of dispersant, 3g of defoaming agent, and 5g of leveling agent to obtain a high-performance coating; apply the high-performance coating to the surface of the high-strength aluminum alloy plate, dry at 50°C for 2h, and continue to dry at 100°C for 2h to obtain the finished product; the reaction mass ratio of isophorone diisocyanate, hydroxypropyl polydimethylsiloxane, microcapsule corrosion inhibitor and dibutyltin dilaurate is 8:80:16:0.1.
[0023] Comparative Example 1: The heat diffusion treatment in step 1 is removed, and the rest is the same as in Example 1, and the specific steps are as follows: Step 1: The aluminum alloy raw material is melted and cast to obtain an ingot; the ingot is then subjected to high-temperature insulation, extrusion molding, and stretching molding in sequence to obtain an aluminum alloy plate; the content of each component of the aluminum alloy raw material is: by mass fraction, 0.9% magnesium, 2.0% silicon, 0.3% iron, 0.5% zinc, 0.2% copper, 0.2% manganese, 0.03% titanium, 0.03% chromium, 0.08% iridium, and 95.76% aluminum; the high-temperature insulation temperature is 550°C; the extrusion molding temperature is 520°C, and the extrusion speed is 30m / min; S1: Chitosan was dissolved in 3.5% acetic acid solution, 4-N,N-diethylaminobenzaldehyde was dissolved in anhydrous ethanol, the two solutions were mixed and stirred at 80°C for 7 hours, cooled to room temperature after the reaction, and then acetone solution was added, and the mixture was allowed to stand, vacuum dried, and ground to obtain Schiff alkalized chitosan; the reaction mass ratio of chitosan to 4-N,N-diethylaminobenzaldehyde was 3:5; S2: Dissolve 1,3-dibromopropane in acetonitrile and triethylamine in anhydrous ethanol, mix the two solutions and stir at 4°C for 3h and 30°C for 15h. After the reaction, perform rotary evaporation, precipitation, washing and freeze drying to obtain quaternary ammonium bromide; the reaction molar ratio of 1,3-dibromopropane to triethylamine is 1:1; S3: Dissolve the Schiff alkaline chitosan and sodium hydroxide in isopropanol, react at -10°C for 15h, then dropwise add quaternary ammonium bromide solution, react at 35°C for 6h, wash and vacuum dry after the reaction to obtain modified chitosan; the reaction mass ratio of Schiff alkaline chitosan, sodium hydroxide and quaternary ammonium bromide is 1:3.2; S4: Add modified chitosan and acetic acid solution to deionized water, stir well to obtain water phase; add 4% volume of emulsifier Span-80 to paraffin, stir well to obtain oil phase; mix the water phase and oil phase, adjust pH to 9.5, then drop vanillin solution to fully cross-link for 8 hours, wash and dry after the reaction to obtain modified chitosan microspheres; add modified chitosan microspheres to 18% sodium tartrate solution, stir well, adsorb at low pressure for 8 hours, wash, centrifuge and vacuum dry after adsorption to obtain microcapsule corrosion inhibitor; the concentration of water phase is 3.5wt%, the volume ratio of water phase to oil phase is 1:16, and the vanillin solution is 0.004wt%; Step 2: Mix N,N-dimethylformamide, isophorone diisocyanate, hydroxypropyl polydimethylsiloxane, microcapsule corrosion inhibitor and dibutyltin dilaurate, and react at 70°C for 5 hours to obtain a silicone-modified polyurethane resin prepolymer; mix 60g of silicone-modified polyurethane resin prepolymer, 30g of silica filler, 3g of dispersant, 3g of defoaming agent, and 5g of leveling agent to obtain a high-performance coating; apply the high-performance coating to the surface of the aluminum alloy plate, dry at 70°C for 3 hours and continue to dry at 120°C for 3 hours to obtain a finished product; the reaction mass ratio of isophorone diisocyanate, hydroxypropyl polydimethylsiloxane, microcapsule corrosion inhibitor and dibutyltin dilaurate is 8:80:16:0.1.
[0024] Comparative Example 2: The preparation steps of the microcapsule corrosion inhibitor are removed, and the rest are the same as Example 1, and the specific steps are as follows: Step 1: Melting and casting the aluminum alloy raw material to obtain an ingot; then the ingot is successively subjected to high-temperature insulation, extrusion molding, and stretching molding to obtain an aluminum alloy plate; the aluminum alloy plate is embedded in a metal diffusion agent, and after sealing, the temperature is first raised to 150°C and maintained for 10 minutes, and then the temperature is raised to 600°C and maintained for 5 hours, and a high-strength aluminum alloy plate is obtained after cooling with the furnace; the metal diffusion agent The content of each component is: by mass fraction, 35% chromium powder, 25% titanium powder, 30% aluminum oxide, 10% ammonium chloride; the content of each component of the aluminum alloy raw material is: by mass fraction, 0.9% magnesium, 2.0% silicon, 0.3% iron, 0.5% zinc, 0.2% copper, 0.2% manganese, 0.03% titanium, 0.03% chromium, 0.08% iridium, 95.76% aluminum; the high temperature holding temperature is 550°C; the extrusion molding temperature is 520°C, and the extrusion speed is 30m / min; Step 2: Mix N,N-dimethylformamide, isophorone diisocyanate, hydroxypropyl polydimethylsiloxane and dibutyltin dilaurate, and react at 70°C for 5 hours to obtain a silicone-modified polyurethane resin prepolymer; mix 60g of silicone-modified polyurethane resin prepolymer, 30g of silica filler, 3g of dispersant, 3g of defoaming agent, and 5g of leveling agent to obtain a high-performance coating; apply the high-performance coating to the surface of the high-strength aluminum alloy plate, dry at 70°C for 3 hours and continue to dry at 120°C for 2.5 hours to obtain a finished product; the reaction mass ratio of isophorone diisocyanate, hydroxypropyl polydimethylsiloxane and dibutyltin dilaurate is 8:80:0.1.
[0025] Comparative Example 3: The preparation steps of the high-performance coating are removed, and the rest are the same as Example 1. The specific steps are as follows: Step 1: Melting and casting the aluminum alloy raw material to obtain an ingot; then the ingot is successively subjected to high-temperature insulation, extrusion molding, and stretching molding to obtain an aluminum alloy plate; the aluminum alloy plate is embedded in a metal diffusion agent, and after sealing, the temperature is first raised to 150°C and maintained for 10 minutes, and then the temperature is raised to 600°C and maintained for 5 hours, and the finished product is obtained after cooling with the furnace; the components of the metal diffusion agent The content is: by mass fraction, 35% chromium powder, 25% titanium powder, 30% alumina, 10% ammonium chloride; the content of each component of the aluminum alloy raw material is: by mass fraction, 0.9% magnesium, 2.0% silicon, 0.3% iron, 0.5% zinc, 0.2% copper, 0.2% manganese, 0.03% titanium, 0.03% chromium, 0.08% iridium, 95.76% aluminum; the high temperature holding temperature is 550°C; the extrusion molding temperature is 520°C and the extrusion speed is 30m / min.
[0026] Hardness test: The finished product prepared by the present invention is used as a sample, and the Vickers hardness of the sample surface is measured using a microhardness tester. The test load is 250 kgf, and the indentation time is 20 s. At least 5 different areas of each sample are measured to reduce errors, and the average value is taken as the final result.
[0027] Corrosion resistance test: The finished product prepared by the present invention was used as a sample and tested by electrochemical alternating current impedance method. A 5% sodium chloride solution was used for corrosion. A platinum electrode was selected as the auxiliary electrode and a silver chloride / silver electrode was selected as the reference electrode. The scanning rate was 0.01 v / s and the standing time was 2 min. The corrosion current density of the sample was tested. This was repeated three times and the average value was taken as the final result.
[0028] Wear resistance test: The finished product prepared by the present invention was used as a sample, and a CFT-I material surface performance tester was used to perform a wear test on the sample. The test used a GCr15 ball with a diameter of 5 mm, a loading force of 1N, a rotation speed of 300r / min, and a friction time of 20min; and then a JB-6C roughness profiler was used to measure the wear profile after friction, and the wear rate was calculated according to the formula. The results are shown in the following table:
[0029] Conclusion: The dosage of Examples 1 to 3 remains unchanged, and only some reaction parameters are modified. From the experimental data, it can be seen that the various properties of the samples have no obvious fluctuations.
[0030] Comparative Example 1: The thermal diffusion treatment in step 1 is removed, and the rest is the same as in Example 1. From the experimental data, it can be seen that compared with Example 1, the Vickers hardness is reduced to 301HV, and the corrosion current density is increased to 0.372×10 -5 The wear rate increases to 1.13×10 -4 The reasons are analyzed as follows: the metal diffusion agent prepared by adding metal chromium powder, titanium powder and alumina in the present invention, the diffusion of chromium and titanium elements can enhance the lattice structure of the aluminum alloy substrate, thereby significantly improving the hardness of the aluminum alloy surface; therefore, after removing the thermal diffusion treatment, the Vickers hardness of the sample is significantly reduced; the corrosion resistance and wear resistance are also reduced.
[0031] Comparative Example 2: The preparation steps of the microcapsule corrosion inhibitor were removed, and the rest was the same as Example 1. From the experimental data, it can be seen that compared with Example 1, the Vickers hardness was reduced to 348 HV, and the corrosion current density was increased to 0.659×10 -5 The wear rate increases to 0.95×10 -4The reasons are analyzed as follows: the microcapsule corrosion inhibitor contains antibacterial and corrosion-resistant components such as Schiff base structure, quaternary ammonium salt structure, sodium tartrate, etc., so it has excellent corrosion resistance. Therefore, after removing the preparation steps of the microcapsule corrosion inhibitor, the corrosion current density increases significantly and the corrosion resistance decreases; the Vickers hardness and wear resistance also decrease.
[0032] Comparative Example 3: The preparation steps of the high-performance coating are removed, and the rest is the same as Example 1. From the experimental data, it can be seen that compared with Example 1, the Vickers hardness is reduced to 336 HV, and the corrosion current density is increased to 0.851×10 -5 The wear rate increased to 3.89×10 -4 The reasons are analyzed as follows: the high-performance coating contains a large amount of components such as silicone, polyurethane, and microcapsule corrosion inhibitors, so it has excellent wear and corrosion resistance; after removing the preparation steps of the high-performance coating, the corrosion current density and wear rate increase significantly, and the corrosion resistance and wear resistance decrease significantly; the Vickers hardness also decreases.
[0033] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0034] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A preparation process of a high-strength wear-resistant aluminum alloy material, characterized in that: The following steps are involved: Step 1: Melting and casting the aluminum alloy raw material to obtain an ingot; then subjecting the ingot to high-temperature insulation, extrusion molding, and stretching molding in sequence to obtain an aluminum alloy plate; embedding the aluminum alloy plate in a metal diffusion agent, and after sealing, heating it to 130-150°C for 5-10 minutes, and then heating it to 550-600°C for 3-5 hours, and then cooling it with the furnace to obtain a high-strength aluminum alloy plate; Step 2: Add the modified chitosan and acetic acid solution to deionized water and stir thoroughly to obtain an aqueous phase; add 3-4% volume of emulsifier Span-80 to paraffin and stir thoroughly to obtain an oil phase; mix the aqueous phase and the oil phase, adjust the pH to 8.5-9.5, and then drop the vanillin solution to fully cross-link for 6-8 hours. After the reaction is completed, wash and dry to obtain modified chitosan microspheres; The modified chitosan microspheres are added to a 15-18% sodium tartaric acid solution, fully stirred, and then adsorbed at low pressure for 6-8 hours. After the adsorption is completed, the microcapsule corrosion inhibitor is obtained by washing, centrifugation, and vacuum drying. Step 3: Mix N,N-dimethylformamide, isophorone diisocyanate, hydroxypropyl polydimethylsiloxane, microcapsule corrosion inhibitor and dibutyltin dilaurate, and react at 65-70°C for 4-5 hours to obtain a silicone-modified polyurethane resin prepolymer; mix the silicone-modified polyurethane resin prepolymer, silica filler, dispersant, defoaming agent and leveling agent to obtain a high-performance coating; apply the high-performance coating to the surface of the high-strength aluminum alloy plate, dry at 50-70°C for 2-3 hours, and continue drying at 100-120°C for 2-3 hours to obtain a finished product.
2. The process for preparing a high-strength wear-resistant aluminum alloy material according to claim 1, characterized in that: In step 1, the contents of the components of the metal diffusion agent are: by mass fraction, 35-40% chromium powder, 20-30% titanium powder, 30-35% aluminum oxide, and the balance is ammonium chloride.
3. The process for preparing a high-strength wear-resistant aluminum alloy material according to claim 1, characterized in that: In step 1, the contents of the components of the aluminum alloy raw material are: by mass fraction, 0.8-0.9% magnesium, 1.5-2.0% silicon, 0.1-0.3% iron, 0.2-0.5% zinc, 0.1-0.2% copper, 0.1-0.2% manganese, 0.02-0.03% titanium, 0.02-0.03% chromium, 0.07-0.08% iridium, and the balance is aluminum.
4. The process for preparing a high-strength wear-resistant aluminum alloy material according to claim 1, characterized in that: In step 1, the high temperature insulation temperature is 450-550° C.; the extrusion molding temperature is 500-520° C. and the extrusion speed is 20-30 m / min.
5. The process for preparing a high-strength wear-resistant aluminum alloy material according to claim 1, characterized in that: In step 2, the preparation process of modified chitosan is as follows: S1: dissolving chitosan in 2.5-3.5% acetic acid solution, dissolving 4-N,N-diethylaminobenzaldehyde in anhydrous ethanol, mixing the two solutions and stirring at 75-80°C for 5-7h, cooling to room temperature after the reaction, adding acetone solution, standing, vacuum drying, and grinding to obtain Schiff alkalized chitosan; S2: Dissolve 1,3-dibromopropane in acetonitrile, dissolve triethylamine in anhydrous ethanol, mix the two solutions and stir at 0-4°C for 2-3h and at 25-30°C for 10-15h. After the reaction, perform rotary evaporation, precipitation, washing and freeze drying to obtain quaternary ammonium bromide; S3: Dissolve the Schiff alkaline chitosan and sodium hydroxide in isopropanol, react at -15~-10℃ for 10-15h, then add quaternary ammonium bromide solution dropwise, react at 25-35℃ for 4-6h, wash and vacuum dry after the reaction to obtain modified chitosan.
6. The process for preparing a high-strength wear-resistant aluminum alloy material according to claim 5, characterized in that: When preparing Schiff-base chitosan, the reaction mass ratio of chitosan and 4-N,N-diethylaminobenzaldehyde is 3:(5-6); when preparing quaternary ammonium bromide salt, the reaction molar ratio of 1,3-dibromopropane and triethylamine is 1:(1.0-1.1); when preparing modified chitosan, the reaction mass ratio of Schiff-base chitosan, sodium hydroxide and quaternary ammonium bromide salt is 1:(3.0-3.5).
7. The process for preparing a high-strength wear-resistant aluminum alloy material according to claim 1, characterized in that: In step 2, when preparing modified chitosan microspheres, the concentration of the aqueous phase is 3-4wt%, the volume ratio of the aqueous phase to the oil phase is 1:(15-18), and the vanillin solution is 0.003-0.005wt%.
8. The process for preparing a high-strength wear-resistant aluminum alloy material according to claim 1, characterized in that: In step 3, when preparing the organosilicon-modified polyurethane resin prepolymer, the reaction mass ratio of isophorone diisocyanate, hydroxypropyl polydimethylsiloxane, microcapsule corrosion inhibitor and dibutyltin dilaurate is 8:80:(15-20):0.
1.
9. The process for preparing a high-strength wear-resistant aluminum alloy material according to claim 1, characterized in that: In step three, the contents of the components of the high-performance coating are: by mass, 50-60 parts of silicone-modified polyurethane resin prepolymer, 20-30 parts of silica filler, 2-3 parts of dispersant, 2-3 parts of defoamer, and 3-5 parts of leveling agent.
10. A high-strength wear-resistant aluminum alloy material, characterized in that: It is prepared according to the preparation process described in any one of items 1-9.
Citation Information
Cited By
Bio-based microcapsule, preparation method and application
CN120838311A
A bio-based microcapsule, method of preparation and use
CN120838311B